2012
DOI: 10.1038/onc.2012.28
|View full text |Cite
|
Sign up to set email alerts
|

Loss of microRNA-143/145 disturbs cellular growth and apoptosis of human epithelial cancers by impairing the MDM2-p53 feedback loop

Abstract: Dysregulated microRNAs (miRNAs) have an important role in many malignant tumors. However, elucidating the roles of miRNAs in cancer biology, especially in epithelial cancers, remains an ongoing process. In this study, we show that both miR-143 and miR-145, which belong to the same miRNA cluster, can negatively modulate expression of their target gene, MDM2. The miR-143 and miR-145 is posttranscriptionally activated by upregulated p53, thereby generating a short miRNAs-MDM2-p53 feedback loop. Re-expression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
151
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(163 citation statements)
references
References 35 publications
9
151
0
3
Order By: Relevance
“…(12,28) Also, many reports have indicated that these miRNAs function as tumor suppressors. (11,12) In this study, we confirmed that the miR-143 ⁄ 145 cluster was significantly reduced in RCC and functioned as a tumor suppressor, similar to its role in other cancers. MiRNAs are unique in their ability to regulate multiple protein-coding genes.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…(12,28) Also, many reports have indicated that these miRNAs function as tumor suppressors. (11,12) In this study, we confirmed that the miR-143 ⁄ 145 cluster was significantly reduced in RCC and functioned as a tumor suppressor, similar to its role in other cancers. MiRNAs are unique in their ability to regulate multiple protein-coding genes.…”
Section: Discussionsupporting
confidence: 77%
“…(7,9,10) According to miRNA signatures, miR-143 and miR-145 are the most frequently downregulated miRNAs in various types of human cancers. (11,12) Both miR-143 and miR-145 are known to be located close together on human chromosome 5q32, where they form a cluster. (13) Several reports have suggested that these clustered miRNAs function as tumor suppressors, targeting several oncogenic genes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, p53 can directly bind the microprocessor complex to stimulate the post-transcriptional processing of another subset of pri-miRNAs exemplified by the bicistronic pri-miR-143/145 without affecting its transcription rate (11,145). miR-34A, miR-143, and miR-145 regulate many target RNAs that likely contribute to p53-related phenotypes (22,24,26,64,68,72,73,129,167). Expression of physiologically relevant levels of miR-34A, miR-143, and miR-145 inhibits cell growth and increases apoptosis, consistent with a role for these miRNAs in the p53 DDR (22,167).…”
Section: Figmentioning
confidence: 99%
“…miR-34A, miR-143, and miR-145 regulate many target RNAs that likely contribute to p53-related phenotypes (22,24,26,64,68,72,73,129,167). Expression of physiologically relevant levels of miR-34A, miR-143, and miR-145 inhibits cell growth and increases apoptosis, consistent with a role for these miRNAs in the p53 DDR (22,167). The full complement of targets of p53-regulated miRNAs has not been determined but together, p53 can presumably regulate the expression of thousands of transcripts and proteins through this mechanism (85).…”
Section: Figmentioning
confidence: 99%